"From Standing Rock to Palestine we are United": diaspora politics, decolonization and the intersectionality of struggles. Issue 7 (28th May 2021) - Salih, Ruba; Zambelli, Elena; Welchman, Lynn
ABSTRACT: This article analyses a form of diasporic activism that breaks the seeming duality between diasporic imaginaries and colonial realities, diasporas and refugees. By focusing on the Palestinian Youth Movement (PYM) it analyses a diasporic standpoint which is not confined to identity politics, nor to the Palestinian nationalist struggle of territorial liberation, but conceives of Palestine as one of the most visible, present-day materialisations of Western colonial modernity. The condition of this diasporic political subjectivity lies in what we call here an "intersectional 'space of appearance'": an affective multi-sited political space that exposes and makes visible the continuum of systems of subjugation and expropriation across liberal democracies and settler-colonial regimes, and the whiteness of mainstream activist spaces. This space encompasses key sites of Black, Indigenous, Arab and Muslim mobilization: from Ferguson to Standing Rock, from the Mexico-US border to Palestine and Palestinian camps, from Tunis to Paris.